STRATEGI INDONESIA DALAM MENGEMBANGKAN PARIWISATA BERKELANJUTAN DI LOMBOK, NUSA TENGGARA BARAT MELALUI DIPLOMASI PARIWISATA HALAL (2016-2021) - Januarystika P. Angela A.S., (2023)
The Halal tourism segment is one of the tourism segments that has recently been quite loved by Muslim communities around the world. With the guarantee of halal in tourism travel, the Muslim community can get a safe and enjoyable holiday experience. In this research, we will see how Indonesia develops halal tourism in Lombok, West Nusa Tenggara and promotes it to Muslim communities in the world. This research will analyze from the perspective of public diplomacy and national branding which will show the scale of Indonesia's success in realizing halal tourism in NTB. In the analysis process used a descriptive qualitative method which can explain more clearly the process behind the development of halal-based sustainable tourism in NTB. Researchers found the fact that the development of halal tourism is going well in NTB, but this growth is not comparable to several aspects of Sustainable Tourism such as the development of the tourism economy in surrounding communities and there are still many aspects of accommodation for tourists that are deficient.